2022
DOI: 10.3390/ijms232113160
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Diagnostic and Clinical Utility of Salivary microRNAs in Traumatic Brain Injury (TBI)

Abstract: Research in traumatic brain injury (TBI) is an urgent priority, as there are currently no TBI biomarkers to assess the severity of injury, to predict outcomes, and to monitor recovery. Small non-coding RNAs (sncRNAs) including microRNAs can be measured in saliva following TBI and have been investigated as potential diagnostic markers. The aim of this systematic review was to investigate the diagnostic or prognostic ability of microRNAs extracted from saliva in human subjects. PubMed, Embase, Scopus, PsycINFO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…A recent systematic review of salivary miRNA/TBI studies ( 31 ) is consistent with the results of our study. Eight of the nine reviewed studies contained exclusively mTBI subjects and seven of the nine involved acute mTBI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent systematic review of salivary miRNA/TBI studies ( 31 ) is consistent with the results of our study. Eight of the nine reviewed studies contained exclusively mTBI subjects and seven of the nine involved acute mTBI.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in plasma or serum miRNAs have been associated with a variety of diseases, including animal (19) and human severe (20)(21)(22)(23)(24)(25) and sport-related TBI (26)(27)(28)(29)(30). A recent systematic review of salivary miRNA in acute mTBI and persistent post-concussion syndrome revealed 14 miRNAs with consistent directional change after mTBI (31). One of the reviewed studies (32) developed a model combining symptoms and neurocognitive measures with miRNAs to aid with the diagnosis of mTBI, however, to date there are no biomarkers by themselves that identify or track acute mild TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large number of publications devoted to the miR study in patients with TBI and various neurodegenerative diseases, some fundamental issues remain unclear in the practical application of miR because its kinetics and the influence of biological factors and identifying of the specific miRs is an extremely difficult task [ 32 , 33 ]. New methods of miR investigation in patients’ saliva significantly increased the rate of obtaining biological material in a non-invasive way thus illustrating the high potential of this direction in the practical field [ 34 ]. Moreover, experimental techniques are being developed in the field of therapeutics of miR-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Specific miRNAs in saliva are altered in individuals with mild TBI and PCS, suggesting that these miRNAs could be used as non-invasive biomarkers for these conditions. At least nine studies have shown 188 differentially expressed miRNAs, of which 30 were detected in most cases [ 50 ]. Di Pietro et al [ 51 ] investigated the role of salivary miRNAs on 1028 elite English rugby union players, by collecting samples during the preseason and standardized head injury assessments at in-game, post-game, and 36–48 h post-game periods.…”
Section: Salivary Biomarkersmentioning
confidence: 99%